Students’ learning outcomes on hydrocarbon materials through mind mapping method - Andriani Andriani; Nelius Harefa; Elferida Sormin; St Fatimah Azzahra (Pascasarjana Universitas Negeri Medan, 2021)
The purpose of this study was to determine the effect of the Mind Mapping learning method on student learning outcomes in class XI MIPA SMAN 1 Siberut Tengah on hydrocarbon material. The research sample amounted to 28 students, who were selected using the Purpose Sampling technique. The instrument used was a test instrument for chemistry learning outcomes, in the form of pretest and posttest which were analyzed using SPSS 22 for window to determine the results of the T-test on the Independent Sample Test. Normality test using Shapiro-Wilk test on sig. > 0.05 that is equal to 0.034. The results of hypothesis testing using the Independent Sample Test which shows that the value of sig. (2-tailed) 0.000 < 0.05, which means Ha is accepted. Thus, it is concluded that there is an effect of using Mind Mapping to improve student chemistry learning outcomes. Keywords: Hydrocarbon materials, learning outcomes, mind mapping method